Análise do suporte a opções flexíveis de suprimento: um estudo em uma empresa do setor de moda - Lipp, Thomás Henrique Petry (Universidade do Vale do Rio dos Sinos, 2011)
A key strategy which is used by the fashion industry is the production’s outsourcing to countries that offer lower costs. One of the draw backs attributed to this strategy is the large lead time for procurement and replacement, caused by geographical distance. Thus, the fashion products´ outsourcing from countries with lower manufacturing cost carries a tradeoff between economic gain and increase the inflexibility of logistics operations, which can generate high risks for losses arising from not assertive demand forecasts. An alternative approach to this trade-off is the use of flexible supply options. In this context, the present research conducts a case study in a company of the Brazilian fashion industry, located in Vale do Rio dos Sinos. The study aims to identify the processes needed to implement this approach and whether the processes identified in the company would be able to provide such support. The research method, based on case study strategy was instrumented by techniques of participant observation, construction of concept maps, and document analysis. As contributions, from the viewpoint of the company, the study identified that the analysed processes in the company would be able to provide support for a flexible supply options approach, but that some of these processes need to be better structured. In order to do so, some recommendations were presented. From the viewpoint of research, it is understood that the contribution was in the seek for establish the appropriate procedure and decision support approaches for flexible supply options, as well as to provide insights for the discussion and for the building of theoretical foundations on the issue of flexible supply options.
Keywords: Terceirização; Opções flexíveis de suprimento; Indústria da moda; Outsourcing; Flexible options supply; Fashion industry; ACCNPQ::Engenharias::Engenharia de Produção